2013
DOI: 10.1136/annrheumdis-2012-202708
|View full text |Cite
|
Sign up to set email alerts
|

Results from a multicentre international registry of familial Mediterranean fever: impact of environment on the expression of a monogenic disease in children

Abstract: Eastern Mediterranean FMF patients have a milder disease phenotype once they migrate to Europe, reflecting the effect of environment on the expression of a monogenic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 17 publications
2
58
0
14
Order By: Relevance
“…The complaints by frequency order in the Turkish FMF study group were reported to be abdominal pain (93%), fever (91.3%), arthritis (58.3%), and chest pain (4%) (10). In another study, it was reported that abdominal pain and fever were on the top of the presenting complaints (19). Fever (100%), abdominal pain (82%), chest pain (43%), and arthritis (37%) were detected in most Arabs (20).…”
Section: M680i(g/mentioning
confidence: 97%
“…The complaints by frequency order in the Turkish FMF study group were reported to be abdominal pain (93%), fever (91.3%), arthritis (58.3%), and chest pain (4%) (10). In another study, it was reported that abdominal pain and fever were on the top of the presenting complaints (19). Fever (100%), abdominal pain (82%), chest pain (43%), and arthritis (37%) were detected in most Arabs (20).…”
Section: M680i(g/mentioning
confidence: 97%
“…The E148Q mutation occurs at a frequency ranging from 1.4-11.4% according to some previous studies. 7,15,16,[19][20][21] Although, there were disagreement regarding whether the E148Q mutation even exhibit disease, it has been reported as disease causing mutation in FMF. 20 Two recent studies from eastern and southeast Turkey reported that the E148Q mutation occurs at frequencies of 34.1% and 30.7% in these populations, respectively, which is approximate to the frequency that we identified at 40.1%.…”
Section: Patient Genotypesmentioning
confidence: 99%
“…2 The M694V mutation was reported to have a relatively severe phenotype, whereas V726A and E148Q have been reported with a milder disease course. [1][2][3]7 FMF is more prevalent among certain ethnic groups such as the Turks, Arabs, Jews and Armenians. 8 Turkey is one of the few countries in the world having high FMF frequency with the estimated prevalence of 1:400 to 1:1000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3]7 La FMF es más prevalente en determinados grupos étnicos como turcos, árabes, judíos y armenios. 8 Turquía es uno de los pocos países del mundo que tiene una alta frecuencia de FMF, con una prevalencia estimada de 1:400 a 1:1000.…”
Section: Introductionunclassified